2004
DOI: 10.1016/j.virol.2004.07.002
|View full text |Cite
|
Sign up to set email alerts
|

The phosphoprotein (P) and L binding sites reside in the N-terminus of the L subunit of the measles virus RNA polymerase

Abstract: Measles virus encodes an RNA-dependent RNA polymerase composed of the L and P proteins. Recent studies have shown that the L proteins of both Sendai virus and parainfluenza virus 3 form an L-L complex [Cevik, B., Smallwood, S., Moyer, S.A., 2003. The oligomerization domain resides at the very Nterminus of the Sendai virus L RNA polymerase protein. Virology 313, 525-536.; Smallwood, S., Moyer, S.A., 2004. The L polymerase protein of parainfluenza virus 3 forms anoligomer and can interact with the heterologous S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
41
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 22 publications
2
41
1
Order By: Relevance
“…Our subsequent linker insertion scan confirmed these data and, by extending successful epitope insertion to distantly related L proteins, illuminated a conserved Paramyxovirus polymerase organization into at least two distinct sections. In addition, we identified an N-terminal position in MeV L, residue 615 located downstream of the N-terminal L-P and L-L oligomerization domain (8,14), that likewise tolerates enlargement without eliminating L bioactivity. This finding did not extend, however, to acceptance of FLAG or HA epitope tags, which contain a high density of charged or bulky aromatic amino acids (75,76) and are thus expected to be structurally more active than the 10-residue linker used in the primary scan.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our subsequent linker insertion scan confirmed these data and, by extending successful epitope insertion to distantly related L proteins, illuminated a conserved Paramyxovirus polymerase organization into at least two distinct sections. In addition, we identified an N-terminal position in MeV L, residue 615 located downstream of the N-terminal L-P and L-L oligomerization domain (8,14), that likewise tolerates enlargement without eliminating L bioactivity. This finding did not extend, however, to acceptance of FLAG or HA epitope tags, which contain a high density of charged or bulky aromatic amino acids (75,76) and are thus expected to be structurally more active than the 10-residue linker used in the primary scan.…”
Section: Discussionmentioning
confidence: 99%
“…These studies highlighted 12 candidate regions in MeV L that were located between CR I and CR VI, received combined propensity scores of Ն4, and were identified by at least two of the algorithms employed. Focusing on the L core, potential interdomain regions located in the N-terminal first 408-amino acid section of MeV L, which mediates both L interaction with the viral P protein and polymerase oligomerization (8,14), and candidates positioned downstream of the LR II/LR III junction (residues 1695-1717 (23, 24)) were not considered for experimental evaluation.…”
Section: In Silico Domain Analysis Of Paramyxovirus L Protein-mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the data do not eliminate other possible scenarios. For example, the L protein of other paramyxoviruses has been shown to oligomerize (26)(27)(28), raising the possibility that the RdRp can contact the Le 3= end and simultaneously have an active site positioned at or near the NS1 GS signal. Another possibility is that the RdRp is able to bind to nt 3 to 12 and then has some mechanism to scan to the first GS signal without first initiating RNA synthesis.…”
mentioning
confidence: 99%
“…Moreover, the SSPE virus-associated mutations in their study were different from those observed for SSPE-Kobe-1 in our study. Cevik et al (11) recently identified a number of mutations in an N-terminal region of the L protein that affected interaction with the P protein. Our present study revealed that SSPE-Kobe-1 did not possess any of those mutations.…”
mentioning
confidence: 99%